PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF PADA MATERI SISTEM KOLOID - Muhammad Akbar; Yudha Irhasyuarna; Rusmansyah Rusmansyah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
ABSTRACT. Has made the development of interactive multimedia instructional media materials colloidal systems. The purpose of this is to facilitate the development of teachers teaching with the use of interactive multimedia instructional media materials colloidal systems. This development is done in class XI IPA 1 SMAN 8 Banjarmasin academic year 2012/2013 which consisted of 12 students as the test sample and the small group of 33 students of class XI IPA 1 SMA PGRI 4 Banjarmasin academic year 2012/2013 as a limited field test sample . Data collection techniques using achievement test techniques, observations, and questionnaires. The test results obtained ahl media iterhadap average of 83.33 including excellent category, student learning outcomes test kecil71 group, 67% in both categories, 80.69% limited field test with the category very well and the average response of students to the test group 43.25 is very good small category and limited field tests 44.18 very good category. That is, the students gave a positive response. This shows an interactive multimedia instructional media can facilitate the learning process in the colloidal system material. Media developed can be used by students as a tool in the learning process.Keywords : interactive multimedia, think, pair, share (TPS), colloidal